Chemical constituents of marine sponge Ianthella basta (Pallas, 1766). Issue 2 (17th April 2022) - Hang, Dan Thi Thuy; Thung, Do Cong; Trang, Do Thi; Yen, Pham Hai; Cuc, Nguyen Thi; Dung, Duong Thi; Tai, Bui Huu; Nhiem, Nguyen Xuan; Van Kiem, Phan
Abstract: Phytochemical study on the methanol extract of the elephant ear sponge Ianthella basta (Pallas, 1766) led to the isolation of one new (named lanthebastanoside A, 1 ) and nine known compounds, holothurin A2 (2 ), desulfoechinoside A (3 ), echinoside B (4 ), holothurin A (5 ), holothurin B (6 ), adenine (7 ), adenosine (8 ), thymidine (9 ), and thymine (10 ). The chemical structures of compounds 1 ‐6 were elucidated by extensive spectroscopic analyses including HR‐ESI‐MS, 1D and 2D NMR, and by comparison of the spectral data with those of previously reported data. Compounds 7 ‐10 were identified by 1 H NMR data and comparing their retention times with authentic samples by HPLC analysis. This is the first report of compounds 2 ‐6 from marine sponge.